2022
DOI: 10.1210/clinem/dgac238
|View full text |Cite
|
Sign up to set email alerts
|

Serum Follicle-Stimulating Hormone and 5-Year Change in Adiposity in Healthy Postmenopausal Women

Abstract: Background Evidence from animal studies suggests that the gradual rise in follicle stimulating hormone (FSH) during reproductive senescence may contribute to the change in adiposity distribution characteristic of menopause. The potential independent role the interrelationships of FSH and estradiol may play in postmenopausal adiposity changes are not well studied. Methods In a sample of 667 postmenopausal women from the Women’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“… 2 , 11 In this regard, FSH has been implicated in contributing to the adiposity and cardiometabolic changes in the postmenopausal period. 13 Prospective studies, such as the Study of Women Across the Nation (SWAN) study, have demonstrated different patterns of change in these hormones surrounding the menopause transition, based in part on body size and race/ethnicity. 14 , 15 For example, estradiol first slowly increases leading up to the perimenopausal stage then sharply decreases within one to two years of menopause in approximately 45% of women, while it slowly declines or remains relatively steady in other women.…”
Section: The Physiology Of Menopausementioning
confidence: 99%
“… 2 , 11 In this regard, FSH has been implicated in contributing to the adiposity and cardiometabolic changes in the postmenopausal period. 13 Prospective studies, such as the Study of Women Across the Nation (SWAN) study, have demonstrated different patterns of change in these hormones surrounding the menopause transition, based in part on body size and race/ethnicity. 14 , 15 For example, estradiol first slowly increases leading up to the perimenopausal stage then sharply decreases within one to two years of menopause in approximately 45% of women, while it slowly declines or remains relatively steady in other women.…”
Section: The Physiology Of Menopausementioning
confidence: 99%
“…In a longitudinal study (667 menopausal women), FSH increased by a maximum of 33.9 mIU/ml in menopausal women who discontinued hormone therapy, and elevated FSH was associated with increases in body fat, body fat mass, and subcutaneous fat percentage ( Mattick et al, 2022 ). However, Wu recently found no correlation between FSH and changes in bone mass and body composition ( Wu et al, 2021 ).…”
Section: Epidemiological Characteristics Of Fsh Level and Body Compos...mentioning
confidence: 99%
“…Large epidemiologic data have shown significant reductions in bone mineral density (BMD) and high resorption rates 2–3 years prior to menopause, when FSH serum levels are increasing, which is also associated with increased body weight and visceral adiposity ( Thurston et al, 2009 ; Senapati et al, 2014 ). A longitudinal study involving post-menopausal women has shown that increases in circulating FSH levels were associated with greater increases in the percentage of total body fat, total body fat mass, and subcutaneous adipose tissue ( Mattick et al, 2022 ). Moreover, clinical studies have found that FSH is also involved in the modulation of lean mass.…”
Section: Introductionmentioning
confidence: 99%